Application of predonation hydration for vasovagal reactions during blood donation: a bibliometric analysis (2004–2023) - Wang, Cong; Chen, Li; Niu, Xiaomin; Shi, Wenwen; Liu, Xiaojing; Li, Meilin; Li, Lihua; Li, Wence (Frontiers in Medicine, 2025)
BackgroundVasovagal reaction (VVR) is one of the prevalent adverse reactions encountered during voluntary blood donation, posing a risk to subsequent donations by the same individuals. Here, we present a bibliometric study aimed at mitigating VVRs.MethodsThis study retrieved pertinent publications on the correlation between predonation hydration and vasovagal reactions from the Web of Science Core Collection (WoSCC) database from 2004 to 2023. Bibliometric analysis was conducted employing bibliometrix R, VOSviewer, and CiteSpace.ResultsThis study encompassed 241 papers across 31 countries and 387 research institutions. Notably, the University of Bucharest (Romania, n = 12, 4.9%), the Australian Red Cross (Australia, n = 10, 4.1%), the University of Queensland (Australia, n = 10, 4.1%), Wayne State University (USA, n = 6, 2.5%), and Ohio State University (USA, n = 5, 2.1%) emerged as the top five contributors in publication output. The journal Transfusion was the most prolific publication venue in this field. Authors Thijsen, Amanda, and Deju, R. were identified as the most prolific contributors in this area. Over the past 3 years, research trends have predominantly focused on fear, complications, management, and hydration.ConclusionThis marks the first comprehensive overview of bibliometric research aimed at understanding the preventive and mitigative effects of predonation hydration on VVR. Predonation hydration as a strategy to prevent or alleviate VVR is currently the focal point of research interest. Our findings suggest that predonation hydration is a promising, low-cost approach to enhance donor safety and retention, although standardization of protocols is needed.